(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2011)
Guerrilla Marketing is low budgeted than heavy advertisement programmes but it provides better result through (WOM) Word-of-Mouth which leads to viral process of marketing. The main objective of Guerrilla Marketing is to make marketing campaign creative & attractive in such a way that people can’t stop talking about it and campaign’s message will spread in the form of chain reaction in target audience. This process needed investment of time, money & efforts which leads to attainment of augmented customer base & profit. The expansion of guerrilla term is self-explanatory for the understanding of guerrilla marketing concept.